2021
DOI: 10.1051/e3sconf/202124701052
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the modified diatomite for treatment of wastewater containing heavy metals

Abstract: The paper studies various modifications of diatomite, aiming at creating sorbents for wastewater purification from heavy metal ions. Diatomite of the Akhmatovskoe deposit of the Penza region was considered as a raw material. The processes of physical and chemical modification of diatomite were investigated. Adsorption isotherms were constructed, quantitative characteristics of adsorption of copper ions on the surface of modified sorbents were obtained. A chemical modification (acidic and alkaline) is proposed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…The predominant sorption of heavy metal ions (Pb +2 , Ni +2 , Zn +2 ) is likely due to the increased ionic metabolism of these clay minerals due to their amorphous structure and high swelling properties, which facilitates the rapid penetration of ions into the underpackage space (Table 4). The lower sorption activity observed in zeolite and diatomite is due to the fact that the rigid frame-zone structure of these minerals does not contain such a large amount of ions capable of ion exchange as previously shown in the work [7,8].…”
Section: Discussion Of the Results Of A Study Of Wastewater Treatment...mentioning
confidence: 59%
See 1 more Smart Citation
“…The predominant sorption of heavy metal ions (Pb +2 , Ni +2 , Zn +2 ) is likely due to the increased ionic metabolism of these clay minerals due to their amorphous structure and high swelling properties, which facilitates the rapid penetration of ions into the underpackage space (Table 4). The lower sorption activity observed in zeolite and diatomite is due to the fact that the rigid frame-zone structure of these minerals does not contain such a large amount of ions capable of ion exchange as previously shown in the work [7,8].…”
Section: Discussion Of the Results Of A Study Of Wastewater Treatment...mentioning
confidence: 59%
“…The main type of galvanic waste is washing water containing a large amount of heavy metal ions [5]. An analysis of existing methods of treatment of natural and heavy metals wastewater has shown that one of the promising is the sorption method using natural inorganic materials as sorbents [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…М.Г.Мурзагалиева 1 , Н.С.Ашимхан 1 * , А.О.Сапиева 2 , А.К Таныбаева 3 , Г.Т.Дарибаева 4 1 С.Д. Асфендияров атындағы Қазақ ұлттық медициналық университеті, Алматы, Қазақстан, 2 Астана Медициналық университеті, Астана, Қазақстан, 3 әл -Фараби атындағы Қазақ ұлттық университеті, Алматы, Қазахстан 4 Алматы технологиялық университеті, Алматы, Қазақстан, e-mail: nazgul.ashimkhan@mail.ru Өнеркәсіптік кәсіпорындардың ағынды суларын ауыр және улы металл иондарынан тазарту дәстүрлі реагенттік әдіспен, сорбциялық және мембраналық технологиялармен жүзеге асырылады. Қарапайым, арзан, қолжетімді және тиімді әдістердің бірі -сорбциялық тазарту болып келеді.…”
Section: ағынды суларды тазалаудың химиялық процестерін зерттеуunclassified
“…Түйінді сөздер: ағынды сулар, табиғи адсорбент, спектрофотометриялық зерттеу, седиментациялық талдау, шөгу жылдамдығы, сорбциялық тазарту, табиғи минералдар Introduction. Decontamination of industrial wastewater from heavy and toxic metal ions is carried out by traditional reagent, sorption and membrane technologies [1][2]. One of the simple, cheap, affordable and highly effective methods is sorption purification.…”
Section: ағынды суларды тазалаудың химиялық процестерін зерттеуunclassified
“…A magnetic heating stirrer was used to impregnate the dry mixture . The sample was then calcined in a muffle furnace at 300 °C to 700 °C for 4 h 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%